The signal strategy in low-carbon supply chains - Xie, Shanshan; Xie, Jiamuyan (Frontiers in Physics, 2026)
IntroductionThis research examines a low-carbon supply chain involving a vertically integrated manufacturer with private market demand information and a retailer that sources low-carbon products. The two parties engage in quantity competition.MethodsWe establish a dynamic signaling game model to analyze how the manufacturer can use its output and carbon emission reduction level signaling demand information to the retailer under asymmetric conditions.ResultsOur findings indicate that (1) the manufacturer must always distort its quantities and carbon emission reduction levels downward to signal low demand; (2) the inference effect worsens the situation of the manufacturer and the retailer; (3) manufacturer’s signaling strategies are influenced by several factors, such as market demand volatility, the prior probability of market demand, its capacity for reducing emission, and consumers preferences for low-carbon products.DiscussionThe novelty of this research lies in incorporating demand information asymmetry into the manufacturer’s output and carbon emission reduction strategies, providing valuable insights for low-carbon supply chains to coordinate the most appropriate signaling strategies.